Micropropagation of Dalbergia nigra, an endangered Brazilian forest tree - Almeida, Rodrigo Oliveira; da Silva, Sarah Santos; Cunha, Ana Catarina Monteiro Carvalho Mori da (Revista Agrogeoambiental, 2021)
We report in this work an in vitro propagation method for Dalbergia nigra using nodal segments from germinated seeds in vitro. Plant material was cultivated on MS medium supplemented with 6-benzyladeninepurine (BAP: 0 μM, 1.11 μM and 2.22 μM) and Naphthaleneacetic acd (NAA: 0.27 μM), combined with different amounts of subcultures for induction of shoot multiplication. Multiplied shoots were inoculated in MS and ½ MS medium (half strength of MS salts) to root, supplemented with NAA (0 μM and 4 μM). Data were analyzed by non-parametric statistical Kruskal-Wallis test. Best results to shoot multiplication were obtained using 1.11 μM or 2.22 μM of BAP combined 0.27 μM of NAA in multiplication medium and performing three subcultures, providing higher rates of shoots production per explant (average of 2.24) and high survival rate. Best results for rooting of shoots generated were obtained using a rooting medium containing ½ MS supplemented with 4 μM of NAA, providing a higher percentage of shoot rooting (average of 68%).